Pengaruh Akreditasi Terhadap Kelengkapan Pengisian Resume Pasien Rawat Inap Di RS PKU Muhammadiyah Yogyakarta Unit I - Fitriana, Syarah Mazaya; , Ibnu Mardiyoko, SKM., MM; , Anisa Catur Wijayanti, SKM., M.Epid (2016)
Medical resume sheets is very important because the medical record documents used in legal protection for medical personnel who commit acts of health care providers and institutions. One of the group accreditation are access to services and continuity of service that contains five (5) sub-group of standardization, one of which is the standard APK.3.2 .1 medical resume full return. This study aims to determine the effect of the accreditation of completeness resume medical sheet in patients at PKU Muhammadiyah Hospital in Yogyakarta. This research method used observational with cross sectional design. The total sample of 360 sheets resume consisting of 180 sheets before to the accreditation survey and 180 sheets after the establishment of accreditation. The sampling technique using systematic random sampling. The bivariate analysis using Fisher's Exact Test test. The results of the bivariate analysis showed that there is no effect between the accreditation of the completeness of social identity (p = 1.000), important reports (1,000), authentication (1,000) and good recording (p = 0.061). There is no effect of accreditation with the completeness sheet resume (p = 1.000).